Towards a Theory and Practice of Religious Literacy: A Case Study of Religion and Belief Engagement in a UK University - Dinham, Adam (Religions, 2017)
This article reports on research undertaken in 2011-2012 into the role of religion and belief in one British university. In this indicative qualitative case study, we observed six important features in relation to religion and belief: a clear divide in attitudes to the place of religion and belief between operations and curriculum; a lack of knowledge and understanding of the religious landscape within the institution; differing and localized responses to religion and belief within and between departments; variation in the approaches of different academic disciplines; very strong desire to promote a good student experience, which included a recognition that some students identify as religious; and that religious and non-religious perspectives are widely conceived of as binary, meaning either secular' or religious. We conclude that these findings demonstrate, at this institution, a struggle to think and act strategically and consistently on religion and belief, and suggest that, because of their influential educational positions, this reflects and reproduces muddled thinking and acting about religion and belief in wider society.